(untitled) (Palíndromo, 2018)
This work looks at the entry of photography into the artistic milieu of Porto Alegre, between the 1960s and 1970s, when Carlos Pasquetti (1948) approached conceptualism, shared with other artists who worked outside the United States and Europe. The counterposition performed by the mechanical means of representation in relation to the regional artistic environment occurs in parallel with the confrontation of the political situation in which the country was. His work, from the outset, presents a duality, an apparent dichotomy between “classical” languages such as drawing and painting, and the use of a new understanding of what would be “appropriate” materials in artistic making. The use of photography by Pasquetti is linked in the first instance to works of conceptual bias, but his work incorporated other elements, which were virtually available in a “panorama” formed by the universe of information that reached the sensitivity of the artist.